2016
DOI: 10.1002/cjce.22650
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the fluid shear rate on the induction time of CO2‐THF hydrate formation

Abstract: A method that allows the effect of the fluid shear rate on the induction time of gas hydrate formation to be characterized was developed and applied to CO2‐THF hydrate formation. The investigation of the effect of the application of a constant shear rate (50 to 300 s−1) to the liquid phase from which the hydrates are formed revealed that the mean induction time decreases significantly as the applied shear rate increases. This could primarily be attributed to a decrease in the time required for stable gas hydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 73 publications
1
6
0
Order By: Relevance
“…Selim et al 23 studied the hydrate induction time a stress/ strain controlled rheometer and found that the hydrate formation induction time increased with the increasing temperature and decreased with increasing pressure, which is the same with the results of other researchers. Also, they conducted the experiments at different ow shear rates and found that higher shear rate could lead to shorter hydrate formation induction time, which could be due to the higher mixing intensity.…”
Section: Introductionsupporting
confidence: 75%
“…Selim et al 23 studied the hydrate induction time a stress/ strain controlled rheometer and found that the hydrate formation induction time increased with the increasing temperature and decreased with increasing pressure, which is the same with the results of other researchers. Also, they conducted the experiments at different ow shear rates and found that higher shear rate could lead to shorter hydrate formation induction time, which could be due to the higher mixing intensity.…”
Section: Introductionsupporting
confidence: 75%
“…In addition, increasing the flow rate can increase the solubility of CO 2 gas in the liquid phase, making the gas− liquid contact more complete, mixing more uniformly, and increasing the number of hydrate nucleation sites. Selim et al 29 studied the hydrate induction time on a stress/strain control rheometer and found that the induction time of hydrate formation increased with temperature and decreased with pressure, which is consistent with the results of other researchers. Similarly, they conducted experiments at different fluid shear rates and found that a higher shear rate can shorten the induction time of hydrate formation, which may be due to higher shear stress leading to a higher degree of mixing.…”
Section: Results and Analysismentioning
confidence: 99%
“…2 A downstream CO 2 capture/conversion technology (CO 2 sink) would reduce the GHG concentration in the atmosphere. To sink CO 2 resulting from fossil fuel combustion, the first stage is CO 2 capture 4,5 and then either its storage 4 or conversion to fuels and chemicals. 6−8 A more or less appropriate approach to decrease CO 2 emissions depends on the sector and follow technological trends.…”
Section: Introductionmentioning
confidence: 99%
“…A downstream CO 2 capture/conversion technology (CO 2 sink) would reduce the GHG concentration in the atmosphere. To sink CO 2 resulting from fossil fuel combustion, the first stage is CO 2 capture , and then either its storage or conversion to fuels and chemicals. A more or less appropriate approach to decrease CO 2 emissions depends on the sector and follow technological trends . For instance, in the transportation sector, electrification through plug-in hybrid electric vehicles (PHEVs) and plug-in electric vehicles (PEVs) equipped with efficient Li-ion batteries , seems a viable option.…”
Section: Introductionmentioning
confidence: 99%